Context Matters, So How Do We Get Better at Working With Context in Implementation Research and Practice?; Comment on "Stakeholder Perspectives of Attributes and Features of Context Relevant to Knowledge Translation in Health Settings: A Multi-country Analysis" - Gillian Harvey (Kerman University of Medical Sciences, 2022)
In the field of implementation research, it is widely recognised that 'context matters.' Attempts to implement innovations, research and new knowledge into practice invariably meet contextual challenges at multiple levels during the process of implementation. The paper by Squires and colleagues provides a detailed insight into the many different features and attributes of context. Yet, as this commentary argues, there are significant challenges ahead if we are to apply our growing understanding about context to improve the practice of implementation in everyday healthcare. This will require attention to the practicalities of working with context to achieve successful implementation.